2015
DOI: 10.3758/s13414-015-0954-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological influences on individual differences in color preference

Abstract: How can the large, systematic differences that exist between individuals' color preferences be explained? The ecological valence theory (Palmer & Schloss, Proceedings of the National Academy of Sciences 107:8877-8882, 2010) posits that an individual's preference for each particular color is determined largely by his or her preferences for all correspondingly colored objects. Therefore, individuals should differ in their color preferences to the extent that they have different preferences for the same color-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…Using a range of images and art types, studies have shown behavioral, physiological (Holmes and Zanker, 2012 ; Gerger et al, 2014 ), and neuronal aspects of art appraisal (Pelowski et al, 2017 ), and have helped to differentiate the processing of aspects of the artwork such as composition, lines, colors, and more top-down meaning and context-derived response (Leyssen et al, 2012 ; Muth and Carbon, 2013 ; Jakesch and Leder, 2015 ; Schloss et al, 2015 ; Lauring et al, 2016 ). Results also show compelling ties to personality and expertise (Furnham and Walker, 2001 ; Chamorro-Premuzic and Furnham, 2004 ; Giannini et al, 2013 ), and have even uncovered compelling reactions notable for art, such as its ability to deliver awe, harmony, anger, transformation, tears, and insight (Silvia, 2009 ; Vessel et al, 2012 ; Hanich et al, 2014 ; Pelowski, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using a range of images and art types, studies have shown behavioral, physiological (Holmes and Zanker, 2012 ; Gerger et al, 2014 ), and neuronal aspects of art appraisal (Pelowski et al, 2017 ), and have helped to differentiate the processing of aspects of the artwork such as composition, lines, colors, and more top-down meaning and context-derived response (Leyssen et al, 2012 ; Muth and Carbon, 2013 ; Jakesch and Leder, 2015 ; Schloss et al, 2015 ; Lauring et al, 2016 ). Results also show compelling ties to personality and expertise (Furnham and Walker, 2001 ; Chamorro-Premuzic and Furnham, 2004 ; Giannini et al, 2013 ), and have even uncovered compelling reactions notable for art, such as its ability to deliver awe, harmony, anger, transformation, tears, and insight (Silvia, 2009 ; Vessel et al, 2012 ; Hanich et al, 2014 ; Pelowski, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some scholars have shown that the average color preference followed a relatively smooth and curvilinear function, with a peak at blue and a trough around yellow or yellow–green. 3 7 Other scholars have found a cross-cultural pattern of sex difference on the color preference, eg, men preferred green and women preferred red. 4 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…The study, in supports the ecological valence theory . To test their theory, k‐means clustering was performed for a cluster size from 2 to 48 (i.e., 48 participants), this was based solely on the pairwise correlations among individuals' preferences for 32 colors.…”
Section: Literature Reviewmentioning
confidence: 88%
“…The results and the subsequent analysis of the cross‐cultural studies not only depend on the scope of the study, but also on the technique used for the analysis of the results. Some techniques are based on data mining and factor analysis while others are statistical such as, canonical correlation, chi‐squared test, and more. The following Table gives a comparison of some of the more related and recent work.…”
Section: Literature Reviewmentioning
confidence: 99%